PERAN GURU SEBAGAI OPINION LEADER DALAM MENGATASI DEGRADASI MORAL SISWA SD NEGERI PARUNGGALIH DI ERA DIGITAL - Novia Herawati Novia; Dewi Sri Andika Rusmana (Jurnal Sosial-Politika, 2022)
The purpose of this study was to find out how the teacher's role as an opinion leader in overcoming the moral degradation of Parunggalih Elementary School students in the digital era. This study uses a descriptive approach by using data collection through observation, interviews, and library research. The development of technology in the digital era is increasingly rapid and difficult to become a challenge in the world of education. Technology causes a shift in values, norms, rules, and morals in students, especially elementary school students. This phenomenon is called moral degradation. SD Negeri Parunggalih students have experienced moral degradation. The absence of accurate filtering allows adult information on the internet to be accessed by elementary school students and causes misunderstandings among students at SD Negeri Parunggalih. The teacher as a figure who has more knowledge than his students should work by providing an understanding of what his students receive. so that students remain in control and do not get lost in the shackles of negative information technology. It was found that there were 5 roles played by the teachers of SD Negeri Parunggalih as opinion leaders in overcoming the problem of moral degradation in the students there. The five roles include: (1) teachers as role models; (2) teachers as educators and mentors; (3) the teacher as a mediator; (4) the teacher as a motivator; (5) and the teacher as a communicator.